Options for Registering Innovative Technologies in Russia - Olga PYATAEVA; Valentina BRITVINA; Elena BORISOVA; Ekaterina BOBROVA; Galina KONYUKHOVA (Communications of International Proceedings, 2021)
Successful capacity-building in science and technology is inextricably linked to the creation of additional opportunities for the use of new knowledge and to making economic agents and national economies more responsive to innovation in general, and to the development of specialist competences, managers of results of intellectual property rights. Technology transfer is strategically important for the effective implementation of innovative technologies, programmes and projects. The need to solve problems in this sphere makes more urgent developing and implementing normative, methodological, organizational and other measures. Activities aimed at improving the efficiency of technology transfer; this is particularly necessary in the sectoral context, in the absence of any established mechanisms suitable for replication. The topicality of this issue for Russian economy is emphasized by the following legislative and regulatory measures: a) the inclusion an item on establishment and activities of Technology Transfer Offices to the passport of new federal project «Science and Universities» (2021-2024); b) strengthening of National Innovation System development activities related to the reform of development institutions under the ВЭБ.РФ ecosystem; c) improving the regulatory framework for innovation (in particular, the enactment of the Federal Law of 31.07.2020 309-F3 «On changes to the Federal Law «Science and State science and technology policy» (in the field of establishment of the acceptable level of financial risk in venture finance); improvement of the existing laws, for example art.5 of the Federal Law «On Insolvency (Bankruptcy)» from 26.10.2002 127-F3, art.103 of the Federal Law «On Education in the Russian Federation» from 29.12.2012.273-F3) and others.
Keywords: Intellectual Property; Technology Transfer; Results Of Intellectual Activity; Intellectual Rights; Innovative Technologies; Means Of Individualization; Intangible Assets; IP Rights Transfer.